Odpowiedzi

2009-11-17T16:49:51+01:00
A)2x+3y=14
3x-2y=8
2x=14-3y/:2
3x-2y=8
x=7-3/2y
3(7-3/2y)-2y=8
x=7-3/2y
21-9/2y-2y=8
x=7-3/2y
-4,5y-2y=8-21
x=7-3/2y
-6,5y=-13/:-6,5
x=7-3/2y
y=2
x=7-3/2*2
y=2
x=7-3
y=2
x=4
y=2

b)1/2x-2y=8
2x+5y=6
1/2x=8+2y/*2
2x+5y=6
x=16-4y
2(16-4y)+5y=6
x=16-4y
32-8y+5y=6
x=16-4y
-3y=6-32
x=16-4y
-3y=-26/:-3
x=16-4y
y=8i2/3
x=16-4*26/3
y=8i2/3
x=16-104/3
y=8i2/3
x=16-34i2/3
y=8i2/3
x=-17i1/3
y=8i2/3

c)1/2x-3/4y=0
2/3x+1i1/4y=9
1/2x=3/4y/*2
1i1/4y=9-2/3x/*5/4
x=3/2y
y=45/4-10/12x
x=3/2y
y=11i1/4-5/6*3/2y
x=3/2y
y=11i1/4-15/12y
x=3/2y
y+5/4y=11i1/4
x=3/2y
9/4y=45/4/*4/9
x=3/2y
y=5
x=3/2*5
y=5
x=15/2
y=5
x=7,5
y=5

d)3x+4y=1i2/3
6x+3y=1i1/4
4y=5/2-3x/*1/4
6x+3y=5/4
y=5/8-3/4x
6x+3(5/8-3/4x)=5/4
y=5/8-3/4x
6x+15/8-9/4x=5/4
y=5/8-3/4x
6x-2,5x=10/8-15/8
y=5/8-3/4x
3i1/2x=-5/8/*2/7
y=5/8-3/4x
x=-5/28
y=5/8-3/4*-5/28
x=-5/28
y=5/8+15/118
x=-5/28
y=0,625+0,127
x=-0,179
y=0,752